2016
DOI: 10.1089/neu.2015.3905
|View full text |Cite
|
Sign up to set email alerts
|

Brain Networks Subserving Emotion Regulation and Adaptation after Mild Traumatic Brain Injury

Abstract: The majority of patients with traumatic brain injury (TBI) sustain a mild injury (mTBI). One out of 4 patients experiences persistent complaints, despite their often normal neuropsychological test results and the absence of structural brain damage on conventional neuroimaging. Susceptibility to develop persistent complaints is thought to be affected by interindividual differences in adaptation, which can also be influenced by preinjury psychological factors. Coping is a key construct of adaptation and refers t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(80 citation statements)
references
References 94 publications
3
77
0
Order By: Relevance
“…Other self-report instruments, such as those developed by Kerr et al (2015) or Montenigro (2016), utilize a structured interview approach that may provide increased accuracy, but is not as easily scaled to large populations or remote (online) participation. Additionally, although these two studies resembled our study most closely in their technique for estimation of cumulative heading, they both relied on differences in player position to augment exposure estimation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other self-report instruments, such as those developed by Kerr et al (2015) or Montenigro (2016), utilize a structured interview approach that may provide increased accuracy, but is not as easily scaled to large populations or remote (online) participation. Additionally, although these two studies resembled our study most closely in their technique for estimation of cumulative heading, they both relied on differences in player position to augment exposure estimation.…”
Section: Discussionmentioning
confidence: 99%
“…Subject self-report questionnaires are a proven method used for quantifying physical activity across a range of recall periods (Atienza & King, 2005; Ekelund et al, 2006; Friedenreich et al, 2006; Johnson-Kozlow, Rock, Gilpin, Hollenbach, & Pierce, 2007). Additionally, self-report measures have been successfully used to quantify repeated head impacts in football players (Kerr et al, 2015; Montenigro et al, 2016). Montenigro et al calculated a cumulative head impact index score based on the players' self report of number of seasons of play at different levels (youth, high school, college) play, weighted by estimates of the frequency of head impacts by position and level of play drawn from published helmet accelerometer studies.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, evidence indicates that serum levels of neurotoxic C-terminal Tau fragments (c-Tau: Fig. 5B) are significantly elevated after mTBI (Shahim et al, 2015). …”
Section: Serological Biomarkers For Brain Injurymentioning
confidence: 99%
“…Shahim et al reported that serum levels of these species were elevated in professional hockey players after concussion, and furthermore found that A-Tau levels were associated with the duration of post-concussion symptoms (Shahim et al, 2014, 2015). Enzyme-linked immunosorbent assays (ELISA) with cut-off values of 12 pg/ml were initially used to investigate serum Tau levels.…”
Section: Serological Biomarkers For Brain Injurymentioning
confidence: 99%
See 1 more Smart Citation